2024
DOI: 10.1186/s13045-024-01541-w
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the gut microbiota in immune responses and cancer immunotherapy

Zehua Li,
Weixi Xiong,
Zhu Liang
et al.

Abstract: The gut microbiota plays a critical role in the progression of human diseases, especially cancer. In recent decades, there has been accumulating evidence of the connections between the gut microbiota and cancer immunotherapy. Therefore, understanding the functional role of the gut microbiota in regulating immune responses to cancer immunotherapy is crucial for developing precision medicine. In this review, we extract insights from state-of-the-art research to decipher the complicated crosstalk among the gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 409 publications
(455 reference statements)
0
0
0
Order By: Relevance
“…We further performed Kaplan‒Meier analyses, which indicated that V. parvula and S. oralis were negatively associated with overall survival in GC patients (Fig. S6), indicating future directions for the use of bacterial markers for predicting overall survival and chemotherapy sensitivity ( 46 ).…”
Section: Discussionmentioning
confidence: 96%
“…We further performed Kaplan‒Meier analyses, which indicated that V. parvula and S. oralis were negatively associated with overall survival in GC patients (Fig. S6), indicating future directions for the use of bacterial markers for predicting overall survival and chemotherapy sensitivity ( 46 ).…”
Section: Discussionmentioning
confidence: 96%